Finite Element Analysis of Static Failure in a Tempered and Hardened 1040 Steel Shaft - Ruviana, R; A N Izzah; M R Firdaus; S T Darmawan; K F Nugroho; W Illaahiyah; I Y Pratama (BIOMEJ, 2025)
This study investigates the static load failure behavior of a shaft made from tempered and hardened AISI 1040 carbon steel using both analytical calculations and numerical simulations. The shaft, with a diameter of 30 mm and length of 350 mm, was subjected to a vertical force of 800 N and torsional moments of 190 Nm and 50 Nm at different ends. Mechanical properties of the material, including a yield strength of 659.10 MPa and ultimate strength of 892.70 MPa, were used to support stress analysis. Analytical methods based on classical mechanics were applied to calculate bending stress, shear stress, von Mises stress, and safety factors. These were then validated through finite element simulation using ANSYS Static Structural. Results showed that the maximum von Mises stress from simulation was 51.5 MPa, significantly below the material's yield strength, while the analytical calculation gave 71.7 MPa. The maximum shear stress was 26.2 MPa in the simulation versus 35.9 MPa analytically. Total deformation reached 0.546 mm in simulation, and 0.0848 mm from manual calculation. The equivalent elastic strain was also within elastic limits in both methods. The safety factor was 12.789 from simulation and 9.27 from manual calculation, indicating a highly safe design. Additionally, the fatigue life analysis revealed the shaft could withstand up to 100 million load cycles without failure. These findings confirm that the shaft remains structurally and functionally safe under the given static and cyclic load conditions.